Asynchronous H∞ control for nonhomogeneous higher-level Markov jump systems. Issue 8 (May 2020) - Yin, Yanyan; Zhu, Lijie; Liu, Fei; Teo, Kok Lay; Wang, Song
Abstract: This paper investigates about asynchronous H ∞ control for nonhomogeneous higher-level Markov jump systems, where a higher-level transition probability matrix is considered. The asynchronous H ∞ controller designed is subject to an independent Markov chain. Using a linear matrix inequality approach, sufficient conditions are established such that system with controller is stochastically stable. A numerical example is presented to demonstrate the effectiveness of our method developed.